‘Prayers of Petition’in the Psalms and West Semitic Inscribed Amulets: Efficacious Words in Metal and Prayers for Protection in Biblical Literature - Smoak, Jeremy D. (Journal for the Study of the Old Testament, 2011)
This article compares several Phoenician and Punic inscribed amulets to the language preserved in several psalms that petition YHWH for protection against evil or other types of danger. The fact that both the amulets and these particular psalms share a similar concern or function, namely, protection against evil, invites such a comparison. It is argued in this article that the similarities between the psalms and the amulets allow for the conclusion that both forms drew from a similar stock of words commonly employed in West Semitic apotropaic religious practices. In particular, it is argued that the protective formulae inscribed on the amulets, which bear certain similarities to the language employed in such psalms, indicate that the psalms contain more reflexes of apotropaic formulae than previously recognized.
paid